DART Creative Lab 2024 - Assis, Paulo de; DART Creative Lab 2024 La Granja de San Ildefonso, Spain 04/19/2024 (DART, Madrid DART, 2024)
Creative Lab with the doctoral students of the DART program.
FRIS
0
Keywords: MetamusicX:Transdisciplinary Encounters in and Beyond Music